Aproksymacja funkcji intensywności zgonów - Sipa, Magdalena; Gnitecka, Renata (The approximation of the force of mortality, 2005)
The mortality analysis of the population is carried out on the basis of the life tables. They include the discreet functions (e.g. death probability function) but their continuous equivalents can be approximated (e.g. the force of mortality). In the paper we have carried out the approximation of the force of mortality on the basis of the data taken from the Polish life tables. In order to do that we have used the analytical distribution of the future lifetime (the simple formula expressing the force of mortality) known from the insurance literature. 3rd order polynomial was also utilized.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 376-386